EXTERNAL ROOT RESORPTION ASSOCIATED WITH ORTHODONTIC TREATMENT: CASE REPORTS AND TREATMENT OPTIONS - Tudor Alexandru Hantoiu; Adriana Monea; Liana Hantoiu; Mariana Pacurar; Monica Monea (European Scientific Journal, ESJ, 2014)
External root resorption was recognized as a late complication of traumatic injuries to the teeth, which usually occurs after orthodontic treatment, orthognatic or dentoalveolar surgery, bleaching techniques or other similar conditions. The purpose of our paper is to discuss the predisposing factors and to present treatment options for teeth with cervical resorption, with emphasys on surgical endodontic approach and prognosis. The study group consisted of 24 patients with an average age of 34 years with 25 cervical defects included in class 1-4 of resorption, according to Heithersay classification. The treatment was nonsurgical in 12 cases (48%), endodontic treatment before surgery in 7 cases (28%) and surgery before endodontic treatment in 6 cases (24% ). Our results showed that the predisposing factors were: orthodontic treatment (39%), trauma (29%), surgery in the cemento-enamel region (20%) and bleeching of teeth (12%). The rates of success for nonsurgical endodontic treatment was 83,3%; for teeth in class 3 and 4 it was recorded in only 17%, in 1 case the resorption continued and 3 teeth were extracted due to root fracture. The conclusions are that teeth with invasive cervical resorption must be under periodic radiological examination, to make sure that the resorptive process had stopped. These teeth have a high risk of fracture and the patients must be instructed to prevent plaque formation in order to avoid periodontal complications.